واقع الأنثروبولوجيا الدينية في الوطن العربي - بنحرزالله, مراد (Changement Social, 2018)
تسعى هذه الدراسة أن تسلط الضوء على تخصص الأنثروبولوجيا الدينية في الوطن العربي فبعد تحديد ماهية الأنثروبولوجيا والإشارة لظهورالأنثروبولوجيا كتخصص علمي في العالم العربي، وتبيان المقصود بالأنثروبولوجيا الدينية عموما، تم الإنتقال بعد ذلك لتسليط الضوء على واقع الأنثروبولوجيا الدينية في الوطن العربي، وللحديث عن واقع الأنثروبولوجيا الدينية في الوطن العربي تم تجزئة هذا العنصر لشقين شق متعلق بالدراسات الغربية للدين في العالم العربي، وشق متعلق بدراسات الأنثروبولوجيين العرب للدين في العالم العربي. This studyseeks to highlight the specialization of anthropology of religion in the Arab world. Afterdeterminingwhatanthropologymeans,  itrefers  to the  scientificappearance of anthropology as a discipline in the Arab world, and illustrate the meaning of anthropology of religion in general, afterthatmoving to shed light on the reality of religiousanthropology in the Arab world, and to talk about the reality of religiousanthropology in the Arabwe division this section to two parts, the first one related to Western studies of religion in the Arab world and the second one related to Arabanthropologistsstudies of religion in the Arab world.